Psychological training to improve psychosocial function in patients with major depressive disorder: A randomised clinical trial. (June 2021) - Knight, Matthew J.; Lyrtzis, Ellen; Fourrier, Célia; Aboustate, Natalie; Sampson, Emma; Hori, Hikaru; Cearns, Micah; Morgan, Julie; Toben, Catherine; Baune, Bernhard T.
Highlights: The present study demonstrated that an experimental intervention improved psychosocial function in patients with MDD. This research highlights the potential efficacy of targeted psychological training in remediating chronic psychosocial deficits. Our findings suggest that cognitive, emotional, and social cognitive function may underlie psychosocial deficits. Abstract: Cognitive and emotional remediation training for depression (CERT-D): a randomised controlled trial to improve cognitive, emotional and functional outcomes in depression The aim of the current study was to evaluate an experimental treatment designed to improve psychosocial function in patients with Major Depressive Disorder (MDD) by reinforcing cognitive, emotional, and social-cognitive abilities. Participants ( N  = 112) with current or lifetime MDD were recruited to participate in a randomised, blinded, controlled trial. Exclusion criteria included diagnosis of a substance abuse disorder, bipolar disorder organic, eating disorders, or illness which affect cognitive function. The treatment involved repeated cognitive training designed to improve cognitive, emotional, and social-cognitive abilities. In training sessions, the principles of cognitive training were applied across cognitive, emotional, and social domains, with participants completing repeated mental exercises. Exercises included critically analysing interpretations of social interactions (e.g., body language), exploring emotional reactions to stimuli, and completing game-like cognitive training tasks. Training sessions placed great emphasis on the application of trained cognitive, emotional, and social cognitive skills to psychosocial outcomes. Outcomes demonstrated significant improvement in psychosocial function, symptom severity, self-reported cognition, and social-cognition. Our findings demonstrate the efficacy of multi-domain cognitive training to improve psychosocial functioning in individuals with MDD. We suggest that the present treatment could be deployed at a lower cost and with minimal training in comparison to established psychological therapies.